3(x-4)+18=-21

Simple and best practice solution for 3(x-4)+18=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)+18=-21 equation:



3(x-4)+18=-21
We move all terms to the left:
3(x-4)+18-(-21)=0
We add all the numbers together, and all the variables
3(x-4)+39=0
We multiply parentheses
3x-12+39=0
We add all the numbers together, and all the variables
3x+27=0
We move all terms containing x to the left, all other terms to the right
3x=-27
x=-27/3
x=-9

See similar equations:

| -6(x-1)=-2x+9 | | 5-w=13 | | -6(x-1=-2x+9 | | 7(2y-10)=42 | | -8g+7=57 | | 10+0.75x=8+0.9x | | x^2+20x+98=7 | | 25+8c=89 | | Y=2x2-4x+5 | | (3x-8)-11x=2 | | 6n+18=54-3n | | 1/2(8+x)=7.5 | | 4t+5t-12=69 | | 5y-2=8y+4 | | 17x-(6x-5)=38 | | -----x25=175 | | (-5+10x)=(9x+1) | | 4.73x+3=42 | | 16x^2-16x-4=0 | | -2(3y+4)=-2(y+4) | | (x+1.5x)12=621.6 | | y=14.6(40)+317.8 | | x+1.5x(12)=621.6 | | y=18.9(40)+145.8 | | x+1.5x=621.6 | | 4(c-3)+2(c-3)=0 | | 0.75x-8=12 | | -13=-2x-1 | | 32=5+x/9 | | 3(a+3)=2(2-a) | | 7x-3+5x-61/3=180 | | t+75=t+28 |

Equations solver categories